Ghrelin as a possible biomarker and maintaining factor in patients with eating disorders reporting childhood traumatic experiences. (3rd May 2021) - Rossi, Eleonora; Cassioli, Emanuele; Gironi, Veronica; Idrizaj, Eglantina; Garella, Rachele; Squecco, Roberta; Baccari, Maria Caterina; Maggi, Mario; Vignozzi, Linda; Comeglio, Paolo; Ricca, Valdo; Castellini, Giovanni
Abstract: Objective: The recent conceptualization of ghrelin as a stress hormone suggested that its chronic alterations may have a role in maintaining overeating behaviors in subjects with eating disorders (EDs) reporting childhood traumatic experiences. The aim of this study was to investigate the alterations of ghrelin levels in patients with EDs, their associations with early trauma, binge and emotional eating, and possible moderation/mediation models. Method: Sixty‐four patients with EDs and 42 healthy controls (HCs) had their plasma ghrelin levels measured and completed questionnaires evaluating general and ED‐specific psychopathology, emotional eating, and childhood traumatic experiences. Results: Participants with anorexia nervosa had higher ghrelin levels than HCs in body mass index (BMI)‐adjusted comparisons. Moreover, patients reporting a history of childhood trauma had higher ghrelin levels. Childhood sexual abuse (CSA), BMI, and self‐induced vomiting were independent predictors of ghrelin levels. Moderation analyses showed that ghrelin levels were associated with binge and emotional eating only for higher levels of childhood trauma. Elevated ghrelin was a significant mediator for the association of CSA with binge eating. Conclusions: These results support the hypothesis that chronic alterations in ghrelin levels following childhood traumatic experiences could represent a neurobiological maintaining factor of pathological overeating behaviors in EDs. Highlights: Patients with eating disorders reporting childhood trauma had higher ghrelin levels than other patients with eating disorders. Childhood sexual abuse, body mass index, vomiting, and binge eating were independent predictors of ghrelin. Ghrelin was positively associated with binge and emotional eating, but only in the presence of childhood trauma; moreover, elevated ghrelin was a significant mediator for the association of childhood sexual abuse with binge eating.